2007
DOI: 10.1371/journal.pone.0001355
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Transgenesis Using Dimerizable Cre (DiCre)

Abstract: Cre recombinase is extensively used to engineer the genome of experimental animals. However, its usefulness is still limited by the lack of an efficient temporal control over its activity. We have recently developed a conceptually new approach to regulate Cre recombinase, that we have called Dimerizable Cre or DiCre. It is based on splitting Cre into two inactive moieties and fusing them to FKBP12 (FK506-binding protein) and FRB (binding domain of the FKBP12-rapamycin associated protein), respectively. These l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 52 publications
3
42
0
Order By: Relevance
“…Detailed in vitro characterization of C3HT101/2-fLuc and VEGF cells showed strong thermal inducibility of the gene switch in the presence of nanomolar concentrations of heterodimerizer, but negligible transgene expression when one or both stimuli are absent. Consistent with previous reports ( Jullien et al, 2007), we found the activity of AP21967 to be approximately one-fifth the activity of rapamycin. However, this compound does not inhibit endogenous mTOR and has less than one thousandth the immunosuppressive activity of rapamycin (Indraccolo et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Detailed in vitro characterization of C3HT101/2-fLuc and VEGF cells showed strong thermal inducibility of the gene switch in the presence of nanomolar concentrations of heterodimerizer, but negligible transgene expression when one or both stimuli are absent. Consistent with previous reports ( Jullien et al, 2007), we found the activity of AP21967 to be approximately one-fifth the activity of rapamycin. However, this compound does not inhibit endogenous mTOR and has less than one thousandth the immunosuppressive activity of rapamycin (Indraccolo et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…If the target gene is essential and the knockout mutant fails to grow as a clone, one can still use the mixed population of the Cre-transfected LoxP knock-in line to identify the mutants under the microscope based on fluorescence and analyze the knockout phenotype in live cells. This strategy can be used in any Cre-LoxP-based technique regardless of how Cre expression is controlled (i.e., by transient transfection as described previously [29,30] and in this work or by conditional expression, as in the case of the DiCre system first developed for mouse genetics [46] and recently implemented in T. gondii and P. falciparum [47,48]). …”
Section: Discussionmentioning
confidence: 99%
“…The small molecule rapamycin induces heterodimerization of FKBP and FRB (110), leading to reconstitution of an active Cre subunit. This method of regulation has been demonstrated to function in vitro (109) as well as in mice (111).…”
Section: Reconstitution Of Active Cre From Fragmentsmentioning
confidence: 99%